Physiotherapeutic recommendations for patients with cystic fibrosis - Oliwko, Elżbieta; Babuśka-Roczniak, Magdalena; Wojtanowska-Kaczka, Magdalena; Lyubinets, Oleh; Roczniak, Wojciech (Journal of Education, Health and Sport, 2020)
Cystic fibrosis is a genetically determined disease. The development of medicine has resulted in an improvement and prolongation of life. Numerous scientific studies support the thesis that maintaining physical performance is a key element of complex treatment. The basis of treatment should be: parallel pharmacological treatment and physiotherapeutic. The aim of this work was to present the physiotherapeutic techniques used in this disease. The main methods of physiotherapeutic treatment include positional drainage, forced exhalation technique, active breathing cycle technique, autogenous drainage, variable bronchial pressure technique and increased respiratory pressure technique. Physiotherapy of the respiratory system is of major importance, the main aim of which is to prevent the deterioration of the already existing respiratory failure. Each of the presented methods of physiotherapy was created thanks to constant search for the perfect technique to cleanse the bronchial tree. This disease has a different clinical course and each technique should be adapted to the individual needs of the patient and the basis of effective therapy is systematic, daily cleansing of the bronchial mucus from the bronchial tree. Physiotherapy applied earlyIn the thoracic region, it is the treatment of choice for patients with cystic fibrosis, improves the quality of life and prolongs the patient's age. Conclusions: 1. There is no effective, causal treatment for cystic fibrosis, and drug treatment comes down to treating complications and often has side effects. 2. Comprehensive physiotherapy is the golden mean in the treatment of cystic fibrosis and significantly prolongs the life of patients. 3. The effectiveness of physiotherapy depends on the time of commencement, regularity and personalization of treatments.